Meta Analisis Pengaruh Penerapan Model Generative Learning Terhadap Hasil Belajar IPA Dan Fisika Peserta Didik - Apriani, Mutia Faizah (Universitas Negeri Padang, 2020)
This study conducted a meta-analysis of eleven articles that discussed the effects of the Generative Learning model on student learning outcomes in the field of Natural Sciences and Physics. The eleven articles were analyzed to produce an effect size using several equations. The Generative Learning Model is applied to several levels of education ranging from elementary, junior high and high school. The results of the analysis of eleven articles obtained effect sizes that vary from 0.312 to 3,291 with moderate to high categories. Eleven articles were analyzed, it shows that the Generative Learning model is the most widely applied in elementary schools. While from the average value of the effect size, the effect of the Generative Learning model on learning outcomes is highest at the junior high level. If viewed from the material used, the Generative Learning model is very suitable for use in Newton's Law material, because it has the highest effect size. So it can be concluded that the Generative Learning model can improve the learning outcomes of Science and Physics of students and can be applied from elementary to high school.